Identification of Medically Relevant Trichosporon Species Based on Sequences of Internal Transcribed Spacer Regions and Construction of a Database for Trichosporon Identification - Sugita, Takashi (American Society for Microbiology, 1999)
The nucleotide sequences of the internal transcribed spacer (ITS) 1 and 2 regions in the rRNA gene were determined by directly sequencing PCR-amplified fragments for all of the species (17 species and five varieties) in the genus Trichosporon. Comparative sequence analysis suggests that six medically relevant species, T. asahii, T. asteroides, T. cutaneum, T. inkin, T. mucoides, and T. ovoides, can be readily identified by their ITS sequences. In addition, the sequence analysis showed that conspecific strains have fewer than 1% nucleotide differences in the ITS 1 and 2 regions overall. Molecular phylogenetic trees are also presented.